A Review on the Health Effects of Pesticides Based on Host Gut Microbiome and Metabolomics - Zhou, Meng; Zhao, Jiang (Frontiers in Molecular Biosciences, 2021)
Due to their large number of applications, the pesticides pose potential toxicity risks to the non-target organisms. In recent years, the studies on the toxic effects of pesticides on non-target organisms, based on their gut microbiome and metabolome, have been continuously reported. As a dense and diverse microbial community, the gut microbiota in the mammalian gut plays a key role in the maintenance of host metabolic homeostasis. The imbalance in the gut microbiota of host is closely associated with the disturbance in the host's metabolic profile. A comprehensive analysis of the changes in the gut microbiota and metabolic profile of host will help in understanding the internal mechanism of pesticide-induced toxic effects. This study reviewed the composition and function of the gut microbiota of host, as well as the analysis methods and applications of metabolomics. Importantly, the latest research on the toxic effects of the exposure of pesticide to host was reviewed on the basis of changes in their gut microbiota and metabolic profile.